1991
DOI: 10.2989/025776191784287574
|View full text |Cite
|
Sign up to set email alerts
|

Agulhas retroflection rings in the South Atlantic Ocean: an overview

Abstract: The most energetic western boundary current rings in the world's oceans are shed from the Agulhas retroflection south of Africa. These are responsible for a considerable transfer of heat, salt and energy from the South Indian Ocean into the South Atlantic. This transfer has important implications for global ocean circulation. In addition, the rings have some important local effects (e.g. on weather and on the Benguela upwelling system) in their passage across the South Atlantic. Since 1983, hydrographic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…The specific layers selected for Table ii-is were determined by those chosen by Hall and Fofonoff (1993). So to the extent that the upper layer KE(z) observed in the Agulhas Retroflection Area is due to the passage of meanders (see, for the GSS: Halkin and Rossby, 1985;Hogg, 1994;Kelly, 1991) and pinched-off rings (Duncombe Rae, 1991;Duncombe Rae et ai., 1996;Olson, 1991), perhaps , or KE( a), are so similar (see also Holland et ai., 1991, p. 416). Recirculations are related to eddy rectification (Hogg and Johns, 1995;Holland, 1978).…”
Section: The Indian Oceanmentioning
confidence: 99%
“…The specific layers selected for Table ii-is were determined by those chosen by Hall and Fofonoff (1993). So to the extent that the upper layer KE(z) observed in the Agulhas Retroflection Area is due to the passage of meanders (see, for the GSS: Halkin and Rossby, 1985;Hogg, 1994;Kelly, 1991) and pinched-off rings (Duncombe Rae, 1991;Duncombe Rae et ai., 1996;Olson, 1991), perhaps , or KE( a), are so similar (see also Holland et ai., 1991, p. 416). Recirculations are related to eddy rectification (Hogg and Johns, 1995;Holland, 1978).…”
Section: The Indian Oceanmentioning
confidence: 99%
“…It is trapping depth rather than the full dynamic depth of the Agulhas ring that is important for the Agulhas water that leaks into the South Atlantic. Observational studies have estimated the trapping depth of Agulhas rings to reach 670-1100 m [McCartney and Woodgate-Jones, 1991;Duncombe Rae, 1991]. Van Sebille et al [2010] found Lagrangian particles to reveal leakage waters down to 1200 m. Hence, a property that can identify Agulhas water to depths of 1000 m or more is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an Eulerian measure is useful. Previous studies have estimated the Agulhas leakage in an Eulerian framework [Duncombe Rae, 1991;van Sebille et al, 2010] using temperature and salinity thresholds to identify warm and saline waters from the Indian Ocean. Yet singular property thresholds are restricted close to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Agulhas rings are known to detach from the Agulhas Retroflection south of Africa in the vicinity of 15 • E to 21 • E and 37 • 30 S to 40 • S (Lutjeharms and Ballegooyen, 1988;Lutjeharms and Valentine, 1988) and are known to contribute warm salty water to the South Atlantic Ocean and influence the Meridional Overturning Circulation (Gordon, 1985;Duncombe Rae, 1991;Duncombe Rae et al, 1996). Improved knowledge of their evolution is needed to understand their scales, translation speeds, and the role they play in the MOC.…”
Section: Introductionmentioning
confidence: 99%